Chaos vibration of pinion and rack steering trapezoidal mechanism containing two clearances. (August 2017) - Wei, Daogao; Wang, Yu; Jiang, Tong; Zheng, Sifa; Zhao, Wenjing; Pan, Zhijie
Highlights: Use a rotation pair model with two state clearance. Establish a dynamic model of pinion and rack steering mechanism with two clearance. Use independent suspension as the prototype. Abstract: The multi-clearances of breaking type steering trapezoidal mechanism joints influences vehicle steering stability. Hence, to ascertain the influence of clearance value on steering stability, this paper takes the steering mechanism of a certain vehicle type as a prototype that can be simplified into a planar six-bar linkage, then establishes the system dynamic differential equations after considering the two clearances of tie rods and the steering knuckle arms. The influence of the clearance parameters on the movement stability of the steering mechanism is studied using a numerical computation method. Results show that when the two clearances are equal, the planar movement of the tie rods changes from period-doubling to chaos as the clearances increase. When the two clearances are 0.25 mm and 1.5 mm respectively, the planar movements of the two side tie rods come into chaos, causing the steering stability to deteriorate. Moreover, with the increase of clearances, turning moment fluctuates more intensively and the peak value increases.